Electronic commerce: E-Commerce - Thongyen, Dr.Chumnan (Journal of Dhamma for Life, 2024)
The purpose of this study is to study the assembly of e-commerce as a channel for distributing goods and services. The study was conducted from academic documents and related research. The results of the study show that the current advances in communication technology, which use the Internet network system, facilitate entrepreneurs and consumers. This reduces costs and wasted time caused by providing and using services very well. This makes it easy to promote the e-commerce business by being able to publicize it all over the world and is a large marketing channel in the world without borders. This makes e-commerce a transaction to buy or exchange goods and services on the Internet or online that can quickly reach the target consumer group directly. This has led to a wider buyer base and less investment budget, Trade without a storefront. They can interact with each other instantly. Trade at any time, this allows them to offer a wide range of transactions, such as sales, sales, and every day without a day off. After-sales Service Transfer of money to pay for goods and transportation services, which is convenient for entrepreneurs and consumers. This reduces the cost and time caused by providing and using services.